2006
DOI: 10.1080/15226510600846749
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Phytoremediation of Polychlorinated Biphenyl-(PCB)-Contaminated Soil

Abstract: Weathered soils contaminated with commercial-grade Aroclor 1260 from three sites in Canada were used to investigate the polychlorinated biphenyl (PCB) phytoextraction potential of nine plant species (Festuca arundinacea, Glycine max, Medicago sativa, Phalaris arundinacea, Lolium multiflorum, Carex normalis, and three varieties of Cucurbita pepo ssp. pepo) under controlled greenhouse conditions. The soils used varied in PCB concentration (90-4200 microg/g) and total organic content (0.06-2.02%). Greenhouse expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 41 publications
8
74
3
Order By: Relevance
“…In these plants, PCB translocation from roots to stalks and from stalks to leaves took place only with respect to trichloro-PCBs congeners. Similarly, Zeeb et al (2006) determined higher levels of PCBs (1.7-288 μg/kg) in the aboveground biomass of Cucurbita pepo, with the highest portion of tetra-, pentaand hexachlorobiphenyls [42]. Sunflower roots had a higher amount of these more chlorinated congeners compared to maize roots.…”
Section: Distribution Of Pcb Congenersmentioning
confidence: 99%
“…In these plants, PCB translocation from roots to stalks and from stalks to leaves took place only with respect to trichloro-PCBs congeners. Similarly, Zeeb et al (2006) determined higher levels of PCBs (1.7-288 μg/kg) in the aboveground biomass of Cucurbita pepo, with the highest portion of tetra-, pentaand hexachlorobiphenyls [42]. Sunflower roots had a higher amount of these more chlorinated congeners compared to maize roots.…”
Section: Distribution Of Pcb Congenersmentioning
confidence: 99%
“…For example, some fruit species have been shown to accumulate BPA and PCBs in their fruit (i.e. Kang et al, 2006;Zeeb et al, 2006). Studies have shown that examining the symbiotic associations of the plants with various bacteria and fungi may be important when determining the uptake capacity of phytoremediators as well.…”
Section: Discussionmentioning
confidence: 99%
“…As stated previously, studies have shown the uptake of PCB's (Zeeb et al 2006;Ficko, Rutter, and Zeeb 2010) and dioxins (Huelster, Mueller, and Marschner 1994) into plant tissue. But PCB metabolism in plants is slow and dioxins have not yet been shown to degrade within the plant (Campanella, Bock, and Schröder 2002).…”
Section: Phytodegradationmentioning
confidence: 99%
“…Alfalfa and other plant species have been shown by several studies to extract PCBs from soil (Ficko et al, 2010;Greenwood et al, 2011;Liu & Schnoor, 2008;Xu et al, 2010;Zeeb et al, 2006). However, PCB degradation within the plant does not appear to be the primary mechanism of phytoremediation.…”
Section: Expected Effectiveness Of Phytoremediation For Cois At Ssflmentioning
confidence: 99%
See 1 more Smart Citation